クライオジェニックサンプラー ヲ モチイタ ショウワキチ ジョウクウ ニオケル セイソウケン タイキチュウ ノ オンシツコウカ キタイ カンソク - 菅原, 敏; スガワラ, サトシ; 豊田, 栄; トヨダ, サカエ; 石戸谷, 重之; イシドヤ, シゲユキ; 森本, 真司; モリモト, シンジ; 橋田, 元; ハシダ, ゲン; 青木, 周司; アオキ, シュウジ; et al. (2010)
P(論文) 南極昭和基地において,気球を用いた温室効果気体の観測を実施した.2003年12月26日と2004年1月5日にそれぞれ気球が放球され,高度10 kmから30 kmにおいて,成層圏の大気サンプルを採取することに成功した.大気サンプルを日本に持ち帰った後に,温室効果気体の濃度とその同位体などの分析が行われた.その結果,二酸化炭素の濃度は,高度20 kmより上空においてほぼ一定となり,その平均濃度を1998年1月に実施した気球観測の結果と比較して,およそ9.7 ppmだけ増加していることが明らかになった.二酸化炭素濃度から成層圏大気の平均年代を推定したところ,高度20 kmより上空での平均年代は,5.0±0.2年であった.過去のデータからも平均年代を推定した結果,その値はほぼ一致しており,南極上空の成層圏の平均年代に長期的な変化はみられなかった.N_2Oのアイソトポマー比は12-1月および1998年1月の観測結果の間で高度分布に異なる特徴が見られ,短期的・長期的な輸送過程の変動の影響が示唆された. Balloon-borne cryogenic samplers were launched from Japanese Antarctic Station, Syowa, on December 26, 2003 and January 5, 2004. Stratospheric air samples were successfully collected at 11 different altitudes from 10 to 30 km. After air samples were transported to Japan, they were analyzed for various greenhouse gases and their isotopes. The CO_2 concentration, thus obtained, shows no significant vertical gradient above 20 km. Secular increase of CO_2 concentration was clearly observable in the mid-stratosphere over Syowa station. From the average CO_2 concentrations in 1998 and 2004, the concentration difference was calculated to be 9.7 ppm, which is almost same the tropospheric trend. The average mean age was estimated to be 5.0±0.2 years above 20 km. This value was almost the same as that estimated from the CO_2 concentration data in 1998, 4.9±0.2 years. This result implies that there is no secular change of the mean age in the Antarctic stratosphere during this period. Vertical distributions of N_2O isotopomer ratios showed different characteristics among December, January, and previous observations in January 1998, showing that the short-term and long-term effects of transport processes. departmental bulletin paper